Investigations of Influence of Rotor Geometry on Cogging Torque in Combined Radial and Axial Flux Permanent Magnet Synchronous Motor - Singh, Gurmeet; Marwaha, Sanjay; Shatru Arora, Ajat (International Journal of Engineering and Technology, 2019)
In this paper, the investigations of cogging torque in combined radial and axial flux permanent magnet synchronous motor (RAFPMSM) has been carried out using 3D FEM modelling. The influence of design parameters and optimizing techniques have been explored to minimize the cogging torque. In the base model of the machine the level of cogging torque, vibration and the noise are elevated due to the additive effect of both radial section and axial section. Both sections have been investigated separately by modelling in FEM. Slot opening, pole arc to pole pitch ratio and the rotor pole configuration are the major design parameters which directly influences the percentage of the cogging torque component in the torque profile of the machine. These design parameters have been targeted and the optimization attempt is made to achieve the goal of minimum Torque Ripple Factor (TRF). The results shown remarkable improvement in the performance from cogging torque view point. The main emphasis has been made on shape of magnets and skewing techniques in both the sections radial and axial. The techniques reflected noticeable improvement in TRF and discernible reduction in vibration. The performance features of high torque density at moderate speed of the machine has been examined and optimized model has been achieved.Â Â